2015
DOI: 10.1159/000381417
|View full text |Cite
|
Sign up to set email alerts
|

Early Mobilization in Ischemic Stroke: A Pilot Randomized Trial of Safety and Feasibility in a Public Hospital in Brazil

Abstract: Background: The effect of early mobilization after acute stroke is still unclear, although some studies have suggested improvement in outcomes. We conducted a randomized, single-blind, controlled trial seeking to evaluate the feasibility, safety, and benefit of early mobilization for patients with acute ischemic stroke treated in a public teaching hospital in Southern Brazil. This report presents the feasibility and safety findings for the pilot phase of this trial. Methods: The primary outcomes were time to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 27 publications
1
25
0
7
Order By: Relevance
“…Results are presented as the OR (95% CI) of the early versus delayed mobilisation group. 65 Bernhardt 35 AVERT 31 Chippala 60 Chippala 63 Poletto 61 Herisson 62 T his project met its initial objectives of effectively delivering our VEM protocol with a resulting change in practice. 30 We observed earlier, more frequent and higher dose (amount of) out-of-bed mobility in terms of sitting, standing and walking activity.…”
Section: Statistical Trial Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results are presented as the OR (95% CI) of the early versus delayed mobilisation group. 65 Bernhardt 35 AVERT 31 Chippala 60 Chippala 63 Poletto 61 Herisson 62 T his project met its initial objectives of effectively delivering our VEM protocol with a resulting change in practice. 30 We observed earlier, more frequent and higher dose (amount of) out-of-bed mobility in terms of sitting, standing and walking activity.…”
Section: Statistical Trial Resultsmentioning
confidence: 99%
“…In our systematic review of similar RCTs, we identified eight eligible trials 25,27,31,[60][61][62][63][64] that currently have data available. Of these eight trials (2618 participants), AVERT provided the most information (2104 participants).…”
Section: Meta-analysis Of Early Mobilisation Trialsmentioning
confidence: 99%
“…A total of 9 articles 5, 6, 15, 16, 1822 met our inclusion criteria and were finally included in this meta-analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 9 RCTs published between 2008 and 2016 including 2,803 participants were examined. Of the 9 included studies, 3 16, 18, 21 were conducted in Europe, 2 19, 20 in Asia, 1 5 in South America, 1 6 in Oceania, 1 22 in 2 countries across Europe and Oceania, and 1 15 in 5 countries across multiple continents. With respect to stroke subtype, 5 6, 15, 16, 19, 22 studies included patients with any stroke type, 3 5, 18, 21 included patients with ischemic stroke (IS) only, and only 1 20 included patients with hemorrhagic stroke (HS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation